Izhma-Komi reindeer herding: ethnic invariants and local variations - Istomin K.V.; Liskevich N.A. (Вестник археологии, антропологии и этнографии, 2017)
This article raises a problem of reindeer herding types. On the basis of ethnographic flieldwork data the authors compare technological traits and herding techniques of the «classical» Izhma-Komi reindeer herding of Bolshezemelskaya tundra to those observed in the easternmost and the westernmost local groups of Komi herders. This comparison shows significant differences in reindeer herding technology between the groups. This raises questions about the exact content of the term «Izhma Komi Reindeer herding» and about the spheres of its application. The analysis shows that this term can refer to 1) a technological system of reindeer herding that existed among the Izhma-Komi of Bolshezemelskaya tundra in the second half of the 19th century, but currently does not exist anywhere; 2) a certain set of herding techniques, which is used by some, but not all modern Komi reindeer herders as well as representatives of other ethnic groups nomadizing in the same environmental zone; 3) common traits of material, spiritual and normative culture, which can be observed in most (but again not all) groups of Komi reindeer herders, can be related to reindeer herding, but they do not form a part of reindeer herding economy in the strict sense. The third meaning of the term makes the most sense, but it makes the application of the notion rather limited as far as the studies of traditional economy are concerned.